PTPRC (CD45) is not associated with multiple sclerosis in a large cohort of German patients - Haupts Michael; Sindern Eckhart; Miterski Bianca; Schimrigk Sebastian; Epplen Joerg T (BMC, 2002)
Abstract Background Since contradictory results have been reported, we reanalysed the 77C→G transition in exon 4 of the protein-tyrosine phosphatase receptor-type C (PTPRC also known as CD45) in a large cohort of German MS patients and controls. Different isoforms of the protein are expressed, depending on alternative splicing of exons 4 (CD45RA), 5 (CD45RB) and 6 (CD45RC) (CD45RO, exons 4-6 spliced out). The 77C→G transition does not change the amino acid sequence, but it is probably part of a motif necessary for splicing leading to the isoform CD45RA. The expression of CD45RA is increased in 77C/G heterozygous individuals. The aim of the study was to clarify the importance of the PTPRC 77C→G transition in our German cohort of MS patients. Methods PCR products of exon 4 were digested using endonuclease MspI. The resulting restriction fragments of the wildtype C allele are 198 and 62 bp in length. In the G allele an additional restriction site is present yielding fragments of 114 and 84 bp. Results The G allele was identified in 10 of the 347 controls (1.4%) and in 7 of 454 MS patients (0.8%; Table 1). No homozygous individuals were found either in the control or in the patient group. Genetic association between the PTPRC 77C→G transition and MS susceptibility was excluded in the MS cohort. In addition, subgrouping patients according to differences in the clinical course of MS or according to HLA-DRB1*15 status did not yield significant differences. Conclusions The 77C→G transition in exon 4 of the PTPRC gene may contribute to MS susceptibility only in very few families, if at all, but it is not relevant for the majority of MS cases, including virtually all German patients.